Making Indonesia Sustainable: Shaping the Law to Reduce Digital Carbon Footprint - Puteri, Dina Silvia (Faculty of Law, Universitas Negeri Semarang, 2024)
Indonesia needs to reduce the carbon footprint from the The Paris Agreement result, a legally binding international treaty on climate change, which entered into force on 4 November 2016. One of the outputs from the Paris Agreement is that the country needs to submit their national climate action plans, known as nationally determined contributions (NDCs). To achieve a sustainable future, Indonesia has Enhanced National Determined Contribution (ENDC) and committed to reducing its carbon emissions by 41 percent by 2030. This commitment is included in the Indonesia Emas 2045 (Golden Indonesia 2045) Program. However, the goals are still focusing on the physical carbon footprint. In the Indonesian Net Zero Emission Goals which needs to be achieved in 2060 the five steps mentioned are increasing the utilization of new renewable energy, reduction of fossil energy, the use of electric vehicles in the transportation sector, increasing electricity use in households and industry, and finally the utilization of Carbon Capture and Storage (CCS). Indonesia also needs to focus on reducing the digital carbon footprint as it currently increases with the usage of digital technologies. The research questions discussed in this paper are how Indonesia currently regulates digital carbon footprint in Indonesia, and what can Indonesia do to reduce digital carbon footprint. This research aims to analyze the current condition and current regulation on digital carbon footprint in Indonesia, and how Indonesian government can learn from other countries to reduce the digital carbon footprint in Indonesia. Methodologies used in this research are normative approach and comparative approach. The output of this research is a regulation to reduce digital carbon footprint in Indonesia, and to regulate the business actors to create ESG reports on a company's sustainability.